THE EFFECT OF COMORBIDITIES ON MORTALITY IN COVID-19 PATIENTS IN dr RADEN SOEDARSONO HOSPITAL PASURUAN: Pengaruh Komorbid Terhadap Mortalitas Pada Pasien COVID-19 yang di RSUD dr. Raden Soedarsono Kota Pasuruan - Lidia Puspita Kencana; Eka Diah Kartiningrum; Elyana Mafticha (Universitas Airlangga, 2023)
Background: COVID-19 patients with comorbidities have the highest mortality risk in Indonesia during the pandemic. Purpose: This study purposed to determine the prevalence of comorbidities on mortality of COVID-19 patients at RSUD dr. Raden Soedarsono, Pasuruan. Methods: This study used a case-control design with 560 samples collected from January until December 2021. The samples consisted of 140 COVID-19 patients who were treated at RSUD dr. Raden Soedarsono, Pasuruan, in 2021 and declared dead as a case group, as well as 420 COVID-19 patients treated at RSUD dr. Raden Soedarsono, Pasuruan, in 2021 but did not die as a control group. The data were then analyzed using a logistic regression test with SPSS 22.0. Results: The results show that almost all COVID-19 patients did not have comorbidities of diabetes mellitus (85.50%), autoimmune (98.60%), kidney disease (98.20%), gastrointestinal diseases (92.10%), thrombosis and coagulation disorders (93.60%), myocardial injury (99.30%), heart failure (94.30%), hypertension (95.20%), and tuberculosis (5.70%). Also, almost all COVID-19 patients did not have comorbidities of geriatrics (71.60%), COPD (64.10%), and mortality status (25.00%). The results of the logistic regression test show that comorbidities of diabetes mellitus (P-value 0.01; OR 1.99) and geriatrics (P-value 0.00; OR 2.82) affect mortality in COVID-19 patients. Whereas comorbidities of autoimmune (P-value 0.84), kidney disease (P-value 0.37), gastrointestinal diseases (P-value 0.73), thrombosis and coagulation disorders (P-value 0.24), myocardial injury (P-value 0.84), heart failure (P-value 0.43), hypertension (P-value 0.93), COPD (P-value 0.86), and tuberculosis (P-value 0.15) do not affect mortality inCOVID-19 patients. Conclusion: Diabetes Mellitus and geriatrics are the most significant comorbidities in causing the death of COVID-19 patients at RSUD dr. Raden Soedarsono, Pasuruan.